Deep highest occupied molecular orbital (HOMO) emitter device structures - BOUDREAULT PIERRE-LUC T; MARGULIES ERIC A; ADAMOVICH VADIM (2025)
The invention relates to a deep highest occupied molecular orbital (HOMO) emitter device structure. Embodiments of the disclosed subject matter provide an organic light emitting diode (OLED) having an anode, a cathode, an emissive layer disposed between the anode and the cathode, and a hole blocking layer disposed between the emissive layer and the cathode. The emissive layer may include a phosphorescent dopant, wherein the phosphorescent dopant has emission with a peak maximum wavelength greater than or equal to 600 nm in a 0.5% doped poly (methyl methacrylate) PMMA thin film at room temperature. The highest occupied molecular orbital HOMO energy of the phosphorescent dopant may be less than or equal to-5.1 eV, and the HOMO energy of the hole blocking layer is at least 0.1 eV lower than the HOMO energy of the phosphorescent dopant. 本申请涉及深最高占用分子轨道(HOMO)发射体装置结构。所公开主题的实施例提供一种有机发光二极管OLED，其具有阳极、阴极、安置于所述阳极与所述阴极之间的发射层以及安置于所述发射层与所述阴极之间的空穴阻挡层。所述发射层可以包括磷光掺杂剂，其中所述磷光掺杂剂在室温下在0.5％掺杂聚(甲基丙烯酸甲酯)PMMA薄膜中具有伴随大于或等于600nm的峰值最大波长的发